A case of relapsed lung abscess caused by Eubacterium brachy infection following an initial diagnosis of pulmonary actinomycosis. (2017) - Yamakawa, Hideaki; Hagiwara, Eri; Hayashi, Masahiro; Katano, Takuma; Isomoto, Kosuke; Otoshi, Ryota; Shintani, Ryota; Ikeda, Satoshi; Tanaka, Kaori; Ogura, Takashi
Abstract: We report a rare case of lung abscess due to Eubacterium brachy . In this case, an analysis of the aspirate from frank pus revealed Gram-positive coccobacilli. We initially strongly suspected lung abscess associated with actinomycosis because of the chronic/recurrent clinical course and radio-pathological findings such as a granuloma lesion. Although a biochemical analysis revealed Actinomyces sp., 16S rRNA gene sequencing and a phylogenetic tree analysis of the isolated strain confirmed the presence of E. brachy . Some cases previously diagnosed as actinomycosis might be correctly diagnosed as E. brachy infection. Clinicians should be aware that additional studies using 16S rRNA gene sequencing are needed to clarify whether pulmonary infection associated with E. brachy is a similar entity to that of chronic granulomatous infection disease in pulmonary actinomycosis.